Artificial Intelligence in Periodontics: A Comprehensive Review - Anuj Singh Parihar; Sumit Narang; Sanjeev Tyagi; Anu Narang; Shivani Dwivedi; Vartika Katoch; Rashmi Laddha (Wolters Kluwer Medknow Publications, 2024)
Periodontal diseases are prevalent worldwide and pose a significant public health burden. With the advent of artificial intelligence (AI), there has been growing interest in leveraging AI technologies to improve diagnosis, treatment planning, and management of periodontal conditions. This review aims to provide a comprehensive overview of the applications of AI in periodontics, including its potential benefits, challenges, and future directions. Fifteen relevant studies were analyzed to explore the role of AI in periodontal disease detection, risk assessment, treatment planning, and patient management. The findings highlight the promising role of AI in enhancing the accuracy, efficiency, and personalized care delivery in periodontics.